The relationship between dimensions of personality, self concept and family influence on students in the FELDA scheme in Johore Malaysia - Yahaya, Azizi (EuroJournals Publishing, Inc., 2009)
The purpose of this study is to identify the relationship between the dimensions of personality, self-concept and family influence. The sample consists of 214 students from two secondary schools in the FELDA settlement in Johor. Random cluster sampling was carried out. A pilot test was carried out to determine the internal consistency of the questionnaire. The assessment instrument used in this study was the Malay version of the Junior Eysenck Personality Inventory (JEPI) which has a reliability level of 0.5739. The Malay version of the Tennessee Self-concept Scale which has a reliability level of 0.8657 was also used. The family influence questionnaire which has a reliability level of 0.7913 was also used in this study to identify the effects of family influence in the aspects of family cohesiveness, religious and moral aspect and freedom aspect. Descriptive statistic and Pearson's Correlation were used to analyze the relationship between the dimensions of personality, self-concept and family influence. The results show a weak relationship between the dimensions of personality and self-concept, and between the dimensions of personality and family cohesiveness. However, there is no relationship between the dimensions of personality and the religious /moral and freedom aspect. The results also show that there is a strong relationship between self-concept and family cohesiveness and a moderate relationship between self-concept and the religious/moral aspect. However, there is no relationship between self-concept and freedom.